Instruments for New Music - Patteson, Thomas (University of California Press, 2021)
Player pianos, radio-electric circuits, gramophone records, and optical sound film—these were the cutting-edge acoustic technologies of the early twentieth century, and for many musicians and artists of the time, these devices were also the implements of a musical revolution. Instruments for New Music traces a diffuse network of cultural agents who shared the belief that a truly modern music could be attained only through a radical challenge to the technological foundations of the art. Centered in Germany during the 1920s and 1930s, the movement to create new instruments encompassed a broad spectrum of experiments, from the exploration of microtonal tunings and exotic tone colors to the ability to compose directly for automatic musical machines. This movement comprised composers, inventors, and visual artists, including Paul Hindemith, Ernst Toch, Jörg Mager, Friedrich Trautwein, László Moholy-Nagy, Walter Ruttmann, and Oskar Fischinger. Patteson’s fascinating study combines an artifact-oriented history of new music in the early twentieth century with an astute revisiting of still-relevant debates about the relationship between technology and the arts. “The smartest book on the German roots of what happened once electricity joined sound to make music and media. Amid profound historical events, technological possibilities were hacked, recordings stopped repeating themselves to perform something new, and the innovative art forms with us today were born.” -DOUGLAS KAHN, author of Earth Sound Earth Signal: Energies and Earth Magnitude in the Arts “A fascinating story of the technological music instrumentarium that not only gives composers and improvisers new sounds and new ways to play but also engages all of us in new social and philosophical insights.” -PAULINE OLIVEROS, Composer and Professor of Practice, Rensselaer Polytechnic Institute “Through meticulous new research, Patteson recovers the forgotten history of early twentieth-century music. This book shows how today’s sounds were born long before the age of electronics.” -TREVOR PINCH, author of Analog Days: The History and Impact of the Moog Synthesizer THOMAS PATTESON is Professor of Music History at the Curtis Institute of Music in Philadelphia. He is also Associate Curator for Bowerbird, a performing organization that presents contemporary music, film, and dance.